Metamodelling in a ontology network - Rohrer, Edelweis; Severi, Paula; Motz, Regina; Díaz, Alicia Viviana (2014)
When designing ontology networks, ontologies can be com- bined through mapping or metamodelling relationships, among others. The coexistence of metamodelling with other kind of relationships in a ontology network leads to identify a set of problems, which are the focus of the present work.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Workshop on Modular Ontologies (8va : 2014, sep. : Río de Janeiro). Proceedings, vol. 1248.
Keywords: ONTOLOGÍAS; MAPEO DE DATOS